Algoritma Sistem Pendukung Keputusan dalam Monitoring Penyelesaian Berkas Perkara Pidana Menggunakan Rule Based Expert Systems dan Teknologi Radio Frequency Identification (RFID): Sistem Pendukung Keputusan - Marfuah, Marfuah (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2017)
Process of handling criminal case files related to a criminal offense is legally regulated by a set of IF-THEN rules that produce a knowledge base to provide a conclusion that is capable of supporting in decision making. The process also sets the time related to the schedule of criminal case files settlement. Thus there is a need for a system that monitors the process of case filecompletion to know the status and time of settlement.RFID technology as a support system performs data readings to facilitate the monitoring system. In the implementation of the system, it needs to formulate logical troubleshooting procedures by building a system algorithm that is represented by using a flowchart which is able to facilitate the development of the system and to clarify the work processes of the system in reasoning to produce accurate information for decision support system.